Biomimetic approaches and materials in restorative and regenerative dentistry: review article - Lamia Singer; Ahmed Fouda; Christoph Bourauel (BMC, 2023)
Abstract Biomimetics is a branch of science that explores the technical beauty of nature. The concept of biomimetics has been brilliantly applied in famous applications such as the design of the Eiffel Tower that has been inspired from the trabecular structure of bone. In dentistry, the purpose of using biomimetic concepts and protocols is to conserve tooth structure and vitality, increase the longevity of restorative dental treatments, and eliminate future retreatment cycles. Biomimetic dental materials are inherently biocompatible with excellent physico-chemical properties. They have been successfully applied in different dental fields with the advantages of enhanced strength, sealing, regenerative and antibacterial abilities. Moreover, many biomimetic materials were proven to overcome significant limitations of earlier available generation counterpart. Therefore, this review aims to spot the light on some recent developments in the emerging field of biomimetics especially in restorative and regenerative dentistry. Different approaches of restoration, remineralisation and regeneration of teeth are also discussed in this review. In addition, various biomimetic dental restorative materials and tissue engineering materials are discussed.